Evaluating the efficacy of pictorial preference assessments with children who engage in food selectivity. (13th October 2022) - Villafaña, Veronica N.; Borrero, Carrie S. W.
Abstract: Preference assessments are used in practice with individuals who engage in food refusal and selectivity to identify foods that a child will readily consume before assessment and treatment. Traditional edible preference assessments may be challenging for children who engage in food refusal or selectivity as the child may not consume foods, but rather engage in inappropriate mealtime behavior simply due to the presence of food. Alternative modality preference assessments, such as pictorial, may offer benefits compared to traditional preference assessment formats (e.g., stimulus preference assessment and paired‐stimulus preference assessment). The use of pictures may reduce any evocative effects of the presence of food and result in choice‐making without inappropriate mealtime behavior. Experiment 1 assessed the correspondence between the hierarchies yielded from pictorial preference assessments (with and without access) to a standard edible preference assessment. Experiment 2 evaluated the accuracy of each preference assessment by presenting foods identified as preferred and non‐preferred to determine if the child would accept them. Results suggested that pictorial preference assessments with access corresponded the most with the traditional edible preference assessment. Also, for one individual, the traditional preference assessment did not accurately identify foods that the participant would consume, while the pictorial preference assessment without access yielded a hierarchy.